STUDENT’S PERCEPTIONS OF THE ROLE OF POETRY IN LEARNING ENGLISH PRONOUNCIATION SKILLS - yossudarso Sudarso; Agung Suhadi; Eki saputra; Fetriani (Teaching English and Language Learning English Journal, 2026)
Abstract This study aims to determine students' perceptions of the role of poetry in learning English pronunciation. This study used a quantitative descriptive method involving students of the English Language Education Study Program at the Muhammadiyah University of Bengkulu as research participants. Data were collected through a questionnaire consisting of 20 statements using a five-point Likert scale. The data obtained were then analyzed using descriptive statistical techniques in the form of average values ​​(means) and percentages. The results showed that students had a positive perception of the use of poetry in learning English pronunciation with an overall average value of 3.77, which is included in the high category. Poetry is considered an effective learning medium because it can help students improve segmental aspects such as vowels and consonants as well as suprasegmental aspects including word stress, rhythm, and intonation. In addition, the use of poetry also has a positive impact on students' affective factors by increasing self-confidence and motivation and reducing anxiety in learning English pronunciation. Based on these findings, it can be concluded that poetry has an important role in supporting the development of students' English pronunciation skills and can be used as an alternative learning medium in EFL classes. Keywords: Student perception, Poetry, Learning English